2019
DOI: 10.4236/as.2019.101009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Organic Manure and Biochar on Cashew Seedling Performance, Soil Properties and Status

Abstract: A nursery experiment was conducted at Cocoa Research Institute of Nigeria to evaluate the impact of manure on cashew seedlings. Treatments consisted of biochar, compost, combination of biochar + compost and a control. Treatments were applied at rate of 0 g (control), 5 g compost, 5 g biochar and 2.5 g each of biochar and compost combination into 5 kg soil in pots, laid out in a completely randomized design (CRD) with three replications. The experiment was monitored for four months in the greenhouse. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Nevertheless, biochar had a greater effect on reducing SIR and HC than slurry. Biocharred materials with micro particles and high surface area decreased soil macro porosity as described by Herath et al (2013) and Nduka et al (2019), where corn stover feedstock and cocoa pod husk feedstock biochar were added to silt loam and sandy soils. These results were in the same manner as those obtained by Sheng and Bao (2014) and Abel et al (2013), who indicated that maize feedstock biochar decreased sandy soil capacity for SIR.…”
Section: Effect Of a Single Application Of Compost Or Biogas Slurry On Soil Hydro-physical Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, biochar had a greater effect on reducing SIR and HC than slurry. Biocharred materials with micro particles and high surface area decreased soil macro porosity as described by Herath et al (2013) and Nduka et al (2019), where corn stover feedstock and cocoa pod husk feedstock biochar were added to silt loam and sandy soils. These results were in the same manner as those obtained by Sheng and Bao (2014) and Abel et al (2013), who indicated that maize feedstock biochar decreased sandy soil capacity for SIR.…”
Section: Effect Of a Single Application Of Compost Or Biogas Slurry On Soil Hydro-physical Propertiesmentioning
confidence: 97%
“…Furthermore, applying biochar increased soil water retention as described by Laghari et al (2015); Uras et al (2012) who reported that biocharred materials had a more significant effect on the moisture content of sandy soil at field capacity which increased by 18%, 21.5% and 50%, respectively. As a result of its porous surface structure and the ability to reduce HC by filling drain pores, biochar raises soil water retention capacity (Kinney et al, 2012;Nduka et al, 2019). Bassouny and Abuzaid (2017) indicated that amending sandy soil with 30, 60 and 90 g kg −1 of biogas slurry augmented sandy soil moisture content at field capacity by 43.17, 60.77 and 86.63%, respectively.…”
mentioning
confidence: 99%
“…In this research, the impacts of biochar include: modification of the soil physical and chemical properties, enhancement of cashew seedling vegetative growth parameters and improved nutrient uptake. And the presence of entomopathogen and bio-control agent indicates crop protection advantage of this bio-fertilizer [38] Fertilizer application has been used to control plant diseases of vegetables and crops. Woltz and Jones [39] reported that tomato studies showed better fusarium wilt control when nitrogen was used in soil with high pH.…”
Section: Research Effortsmentioning
confidence: 99%
“…Biochar has also been shown to influence a range of soil chemical properties. Thus, the soil's cation exchange capacity (CEC), pH and electrical conductivity increase (Blackwell et al 2009;Gul et al 2015;Romdhane et al 2019;Singh et al 2022), the soil nutrient retention, nutrient content and quality in the soil become consolidated (Chan et al 2008;Kookona et al 2011;Zambon et al 2016;Li-li et al 2017;Nduka et al 2019).…”
Section: Introductionmentioning
confidence: 99%